Thrombotic Depositions on Right Impeller of Double‐Ended Centrifugal Total Artificial Heart In Vivo. Issue 5 (23rd November 2016) - Karimov, Jamshid H.; Horvath, David J.; Okano, Shinji; Goodin, Mark; Sunagawa, Gengo; Byram, Nicole; Moazami, Nader; Golding, Leonard A.R.; Fukamachi, Kiyotaka
Abstract: The development of total artificial heart devices is a complex undertaking that includes chronic biocompatibility assessment of the device. It is considered particularly important to assess whether device design and features can be compatible long term in a biological environment. As part of the development program for the Cleveland Clinic continuous‐flow total artificial heart (CFTAH), we evaluated the device for signs of thrombosis and biological material deposition in four animals that had achieved the intended 14‐, 30‐, or 90‐day durations in each respective experiment. Explanted CFTAHs were analyzed for possible clot buildup at "susceptible" areas inside the pump, particularly the right pump impeller. Depositions of various consistency and shapes were observed. We here report our findings, along with macroscopic and microscopic analysis post explant, and provide computational fluid dynamics data with its potential implications for thrombus formation.